Research SAP Acceptance Rate Analysis At PT. Pindodeli Uses The Technology Acceptance Model (TAM) Approach - M. Wahidin; Jajang Jajang; Anggi Elanda; Charlie Khowirantio (LPPM STMIK Rosma, 2021)
This study discusses the analysis of the SAP acceptance rate at PT Pindodeli using the TAM approach. The purpose of this study was to determine the acceptance of the SAP system for Pindodeli employees and to determine the factors that affect the acceptance of the SAP system for PT Pindodeli employees. The method used in this research is the Technology Acceptance Model (TAM). The population in this study were 130 employees of PT Pindodeli from 6 Units / Sections, namely Finished Goods, IT, Financing, Logistics, Customer Service, and Purchasing. The sampling technique used by researchers is probability sampling and uses a descriptive approach. The total respondents who got were 61 out of 130 employees. Calculation of data carried out in this study is smart PLS. Hypothesis testing in this study was conducted to test the effect of system service usability and ease of use. The research results prove that usability has a positive and significant effect on SAP system acceptance and ease of use has a positive and significant effect on SAP system acceptance.